Principles of basic construction economics in the 21st century - Ebekozien, Andrew; Aigbavboa, Clinton (Emerald Publishing Limited, 2024)
Principles of Basic Construction Economics in the 21st Century unravels and takes account of the widening and more sophisticated cost management and control services required by the discerning client in today's construction industry. The book will effectively meet the needs of practitioners in the built environment discipline by providing the breadth of knowledge needed to make informed judgments on the many diverse matters within this subject and to achieve economical, sustainable construction. The book reflects the essential aspects of construction economics required to meet the changing construction needs in the context of developing countries in the 21st century. It covers the construction industry and economics and its relationship to the study of building costs; the broad view of approximate estimating and design variables; cost planning, control, and analysis of a construction project; the nature of cost and cost-in-use. In the construction industry, cost indices, property valuation, and the developer's budget play a significant role achieving smart and sustainable construction in the 21st century. Principles of Basic Construction Economics in the 21st Century is essential reading not only for Quantity Surveying and Construction Economist practitioners and students but for all construction-related professionals such as architects, builders, estate surveyors, engineers, property managers, urban planners, and surveyors. The book also has the potential to support construction management and civil engineering courses that are desperately needed in developing economies.
Includes index.
Keywords: Architecture -- Buildings / General.; Building redevelopment, retrofitting, refurbishment.; Architectural structure and design.; Security and fire alarm systems.; Architecture -- 21st century.; Architecture -- Economic aspects.; elektronické knihy; electronic books